Pengaruh Disiplin Kerja ,Stress Kerja, Beban Kerja dan Pengalaman Kerja terhadap Prestasi Karyawan Pada PT. Sat Nusapersada Tbk Batam - M. Arpah; Mohammad Aras (International Forum of Researchers and Lecturers, 2025)
Logical thinking is a fundamental competency for prospective teachers, as it supports systematic reasoning and professional decision-making. This study aimed to analyze the relationship between academic communication and emotional regulation with the logical thinking skills of students at the Faculty of Teacher Training and Education, Satya Wiyata Mandala University, Nabire, Central Papua. A quantitative correlational design was employed with 100 students selected through proportional random sampling. Data were collected using an academic communication questionnaire, an emotional regulation scale, and a logical reasoning test, and analyzed through Pearson correlation and multiple regression. The findings indicate that both academic communication and emotional regulation have positive and significant relationships with logical thinking skills, both partially and simultaneously. These results emphasize that logical thinking development in higher education requires the integration of cognitive, interpersonal, and emotional competencies.